Indeks Perilaku Ketidakpedulian Lingkungan Hidup (IPLKH) Anggota Organisasi Kemahasiswaan Universitas Respati Yogyakarta - Elisabeth Deta Lustiyati; Nur Alvira Pasca Wati; Yelli Yani Rusyani; Jati Untari (MEDIA ILMU KESEHATAN, 2023)
Background: One of the objectives of the 13th SDG is is to take urgent action to address climate change and its impacts. Higher education is the highest educational institution that has an important role in a sustainable future. Objective: This research aims to obtain and evaluate the environmental ignorance behaviour of students who are members of student organizations at Universitas Respati Yogyakarta. Methods: The method in this study is descriptive quantitative to measure the Environmental Ignorance Behaviour Index (EIBI). This research was conducted at October 2022. Results: The highest ignorance index is the dimensions of water saving and transportation usage, which is 0.67. Sharing value of environmental ignorance behaviour comes from the use of transportation (29.57%), water saving (29,52%) and energy management (18.10%). Conclusion: The dimensions of the use of transportation and water saving make a high contribution to the Environmental Ignorance Behaviour Index of student organization members.